2017
DOI: 10.24326/asphc.2017.5.4
|View full text |Cite
|
Sign up to set email alerts
|

EXTENDING POSTHARVEST QUALITY ATTRIBUTES OF GRAPES (V. vinifera L. cv. ‘THOMPSON SEEDLESS’) BY PREHARVEST CALCIUM PULVERIZATIONS

Abstract: Demand for fresh grape is increasing globally in accordance with the improvement in living standard since the grape berry contains large amounts of phytochemicals including anthocyanins, phenolics, flavonoids and resveratrol, which have been suggested to be responsible for human health benefits. However, table grapes easily undergo deterioration due to their soft texture and the high water content, which make it difficult to preserve without treatment. This study was thus conducted to evaluate the effect of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
1
4
1
Order By: Relevance
“…'Red Globe'. Results for changes in TA are similar to findings reported by [28] that berry TA underwent a progressive decrease during storage for cv. 'Thompson Seedless'.…”
Section: Quality Losses Along the Supply Chainsupporting
confidence: 88%
See 2 more Smart Citations
“…'Red Globe'. Results for changes in TA are similar to findings reported by [28] that berry TA underwent a progressive decrease during storage for cv. 'Thompson Seedless'.…”
Section: Quality Losses Along the Supply Chainsupporting
confidence: 88%
“…'BRS Isis' after 50 days in cold storage plus 5 days under ambient conditions. In 2018, however, results indicated that berry color became lighter, which differs from [28] reporting that L decreased with storage time for cv. 'Thompson Seedless', while [55] reported no significant changes in color for cv.…”
Section: Quality Losses Along the Supply Chaincontrasting
confidence: 59%
See 1 more Smart Citation
“…Berry decay was quantified by counting the number of decayed berries in each cluster, multiplying the total number of decayed berries per replication by the average berry size, and calculating the percentage of decayed berries (Sabir and Sabir 2017).…”
Section: Decay Incidencementioning
confidence: 99%
“…After a short time, a lot of xylem sap can bleeding (more than 100 mL•h − 1 ) [27]. For rich nutrient in xylem sap, the loss of these sap may lead to damage of the growth and fruitfulness.…”
Section: Introductionmentioning
confidence: 99%